An indispensable revolution for Pakistan, the beginning of robot assisted MIMVS - Amna Zaheer; Daniyah Zehra Hussain (Journal of the Pakistan Medical Association, 2023)
Madam, Minimally invasive surgical (MIS) techniques or ‘sternal sparing’ strategies, performed by making minor right chest incisions, were introduced in the mid-1990s [1,3]. From that point forward, there has been a decrease in surgical injury and postoperative recuperation, coming about in expanded acknowledgement of these approaches. It works on three essential standards: rebuilding and conserving MV pamphlet portability, creating a vast flyer coaptation surface, and remodeling of the mitral annulus to supply an ideal and steady orifice area. [1] The history of MIMVS expanded from the 1990s when minimally invasive approaches such as the parasternal incision, hemi sternal incision and the mini thoracotomy were investigated by autonomous groups led by Delos Cosgrove and Lawrence Cohn. Further advancements include the primary video-directed repair and substitutions performed through a mini-thoracotomy and the primary utilization of end balloon clamping. Later, improvements incorporated the coming of stereoscopic 3D video endoscopy and mechanical surgery. [5] Robotic technology facilitates complex surgical procedures on the mitral valve without opening the chest. The most significant advantage is diminished surgical injury, which deciphers into early recuperation. In 1998, robotic mitral valve repair was initiated and adopted in 2005 by the US following the first multicenter trial. In classic robotic mitral valve surgery, femoral-femoral cardiopulmonary machine cannulation is performed through a small incision in the groin. The surgeon leading the robotic mitral valve surgery must have the relevant heart surgery certification from the country’s certifying institution. The console surgeon should be experienced in all aspects of mitral valve surgery and be highly versed in repair techniques as robotic procedures take longer than traditional surgeries, especially during the learning curve. Apprenticeship in the so-called mini-mitral using conventional videoscopy is also an advantage, but not a mandatory requirement The courses on robotic mitral valve surgery including formal didactic and practice-oriented training should be obtained by the lead surgeon and the team. Virtual stimulators and wet labs should be provided by the hospital to the team to practice their first 8-10 cases until they gain expertise —Continue